Design and optimization of a compact rectangular galfenol-based magnetostrictive energy harvester - Gandia, David; Gómez-Hurtado, Jorge; Beato-López, J.J.; Garaio, Eneko; Royo-Silvestre, Isaac; Vargas-Silva, Gustavo; Gómez-Polo, Cristina (Sensors and actuators. A. Physical., 2025)
Electromagnetic vibration energy harvesters are widely explored as low-cost and robust solutions for powering wireless and low-power electronics. Based on Faraday’s law, energy generation relies on the modification of the magnetic field distribution within a magnetic element caused by mechanical vibrations inducing an electromotive force (EMF) in a pick-up coil. Within cantilever-based approaches, most harvesters employ rectangular, U-shaped or V-Shaped beams coupled with active materials, coils and permanent magnets, with varying levels of complexity and efficiency. In this work, we present a magnetostrictive harvester based on a rectangular iron cantilever with a bonded Galfenol layer and two cubic magnets, to collect the energy of one dimensional vibrations, optimized through Finite Element simulations and experimental testing. Finite Element Method (FEM) is used to explain the harvester behavior. Magnetic modeling enabled accurate estimation of the H-field inside the Galfenol, guiding the system toward the optimal bias field (∼8 kA/m), while mechanical simulations provided insight into internal stress distribution. This dual modeling strategy not only supported the experimental results but also can be used to design efficient magnetostrictive harvesters for real-world applications. Thanks to the to the refinement process, the resulting design, despite its simplicity, delivers a peak power density of 2.12 mW/cm³ at 40 Hz resonance, demonstrating performance comparable to that of significantly more complex magnetostrictive harvesters. [Display omitted] •FEM guides bias field and stress optimization in a Galfenol harvester.•Simple rectangular design achieves 2.12 mW/cm³ at 40 Hz resonance.•Dual FEM modeling matches experimental voltage and stress results.•Accurate bias field estimation is key to maximizing output.•Compact 0.76 cm³ harvester is suitable for IoT and sensor integration.